Every deep-drawn breath : a critical care doctor on healing, recovery, and transforming medicine in the ICU - Ely, E. Wesley (Scribner, 2021)
"'Every Deep-Drawn Breath' is a . . . blend of science, medical history, . . . patient stories, and personal reflection. Dr. Wes Ely's mission is to prevent patients from being inadvertently harmed by the technology that is keeping them alive. . . . For decades, millions of ICU survivors left the hospital with disabling symptoms including newly acquired dementia, depression, PTSD, and nerve damage, all now recognized as Post Intensive Care Syndrome, or PICS (a severe subset of long COVID symptoms). Dr. Ely's . . . investigations advanced the understanding of PICS and introduced . . . changes that reshaped intensive care: minimizing sedation, maximizing mobility, attending to the family, and providing supportive aftercare"--Provided by publisher.